Ninth Asia Oceania Forum for Synchrotron Radiation Research. Issue 2 (3rd March 2016) - Siu, Karen; Sharp-Paul, Nick
Abstract : Synchrotron users and experts from around the Asia Oceania region gathered in Melbourne in November 2015 for the Ninth Asia Oceania Forum for Synchrotron Radiation Research (AOFSRR). The meeting was held in conjunction with the Australian Synchrotron's annual User Meeting, and the two events shared a joint program of stimulating presentations over three full days.